Female Solo Self-Employment in Germany: The Role of Transitions and Learning From a Life Course Perspective - Haasler, Simone R.; Hokema, Anna (Social inclusion, 2022)
Based on a qualitative analysis of 12 solo self-employed women’s work biographies, this article investigates the (re)structuring effects of solo self-employment on the professional and private lives of women in Germany in their mid- and late-career stages. While solo self-employment has been gaining significance in the German labour market in the last two decades, it is largely an underresearched subject from the perspective of female labour market participation. Our study shows that the transition to working solo self-employed constitutes a marked break in female work biographies with lasting restructuring effects on their life courses. Constituting a deviation from the female standard life course, this move can be understood as a coping strategy of biographical discontinuities, which translates into specific patterns against the background that women (still) assume most of the care and housework responsibilities. How the transition to solo self-employment is being prepared and managed and what role learning and risk management play in the transition process is the focus of our article. Our aim is to better understand the underlining rationalisation logics of female solo self-employment in terms of labour market participation, reconciling work and family life, and professional self-realisation. While in the German welfare system solo self-employed bear higher risks of precarity and financial old age insecurity, solo self-employment is functional as an individual strategy for action, giving women the opportunity to do justice to their (mid) life courses and intrinsic needs to pursue both professional work and freedom of choice when and how to work. This may act as a corrective for gender inequalities in the world of work, especially when it comes to working in a self-determined way.